Pengaruh Lingkungan Kerja dan Komitmen Terhadap Kinerja Karyawan pada Unit Usaha Otonom Agribisnis Toraja Kecamatan Mengkendek Kabupaten Tana Toraja - Unde, Juliet Triani; Ruma, Zainal; Burhanuddin, Burhanuddin; Kurniawan, Agung Widhi; Hamka, Rezky Amalia (Jurnal Akuntansi Pajak dan Manajemen (TAJAM), 2025)
This research aims to determine the influence of the work environment and commitment on employee performance at the Toraja Agribusiness Autonomous Business Unit, Mengkendek District, Tana Toraja Regency. This research approach uses a quantitative approach. The sample used was 75 respondents. Data collection techniques using observation methods, questionnaires, interviews, documentation. The data analysis technique used is test. The data analysis technique used is validity test, reliability test, classical assumption test and multiple linear regression using Statistics and Service Solution (SPSS) version 25 Based on the results of the research that has been conducted, it shows that the work environment variable (X1) and the Commitment variable (X2) simultaneously have no effect on the employee performance variable (Y). Furthermore, the work environment variable (X1) partially has no influence on employee performance with the calculated value of tcount 0.631 < ttable 1.993 and a significant value of 0.530 > 0.05. The commitment variable has an influence on employee performance with the calculated value of tcount 2.072 > ttable 1.993 and a significant value of 0.042 < 0.05. So that employee commitment to the Toraja Agribusiness Autonomous Business Unit has a greater contribution to improving performance compared to the work environment in the context of the agribusiness autonomous business unit.